2017
DOI: 10.1002/2017ja024126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar irradiance on the upper ionosphere and oxygen ion escape at Mars: MAVEN observations

Abstract: We present multi‐instrument observations of the effects of solar irradiance on the upper Martian ionosphere and escape fluxes based on the Mars Atmosphere and Volatile EvolutioN (MAVEN) data from November 2014 to February 2016. It is shown that fluxes of oxygen ions with E > 30 eV both inside and outside of the Martian magnetosphere are nonsensitive to EUV variations. In contrast, the fluxes of ions with lower energies extracted from the upper ionosphere increase with solar irradiance. Such an enhancement is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 47 publications
(61 reference statements)
6
49
1
Order By: Relevance
“…When compared to previous results, these first estimates based on MAVEN data seem to be significantly lower, something that could be related to the weakness of solar cycle 24 which translates into lower EUV fluxes and, as different authors have pointed out, this leads to lower ionospheric escape (e.g., Dong et al, , ; Dubinin et al, ; Ramstad et al, ). In addition to these cyclical variations, the location where the ions are measured, the energy ranges included in the analyses, and in general the way data are treated differ among the studies and are also a cause of the observed variations that span over 2 orders of magnitude.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…When compared to previous results, these first estimates based on MAVEN data seem to be significantly lower, something that could be related to the weakness of solar cycle 24 which translates into lower EUV fluxes and, as different authors have pointed out, this leads to lower ionospheric escape (e.g., Dong et al, , ; Dubinin et al, ; Ramstad et al, ). In addition to these cyclical variations, the location where the ions are measured, the energy ranges included in the analyses, and in general the way data are treated differ among the studies and are also a cause of the observed variations that span over 2 orders of magnitude.…”
Section: Introductionmentioning
confidence: 48%
“…The vertical axis corresponds to the Z axis while the horizontal one corresponds to the magnetic field as measured by the MAG instrument at distances along the X axis between −2 and −1 R M . This coordinate system allows for a better separation of the regions occupied by the planetary ions of different origin (Dubinin et al, ).…”
Section: Ion Escape As Detected By Mavenmentioning
confidence: 99%
“…Strong induced magnetic fields are required to balance the solar wind, providing a hypothetical explanation: The corresponding powerful J × B forces could collect nearly all outflowing ions in a plasma sheet compressed by the same forces to the point that it might have been completely missed on MEX orbit #9606, despite traversing deep into the tail. Indeed, accelerated populations are largely confined to the plasma sheet as recently shown by Dubinin et al () and increased n sw redistributes the cold ion outflow to accelerated populations (Ramstad, Barabash, Futaana, Nilsson, et al, ). Similar changes in ion distributions during CMEs are also seen in models (Luhmann et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…Effects of a weak intrinsic magnetic field on atmospheric escape from Mars. Geophysical Research Letters, 45, 9336-9343. https://doi.org/10.1029/ 2018GL079972 recent MAVEN mission revealed that the low-energy (<30 eV) O + escape rate increases to a few times 10 25 s À1 under solar EUV irradiances higher than 0.1 W/m 2 (Dubinin et al, 2017). Some numerical simulations also investigated the effect of the solar conditions on the ion escape rate.…”
Section: Citationmentioning
confidence: 99%